INCREMENTAL BUDGETING IN BUDGET ALLOCATION FOR TEACHER PEDAGOGIC COMPETENCY DEVELOPMENT AT MADRASAH IBTIDAIYAH AL-ADLI PALEMBANG: Incremental Budgeting dalam Alokasi Anggaran untuk Pengembangan Kompetensi Pedagogik Guru Di Madrasah Ibtidaiyah Al-Adli Palembang - Mira Marisa Mira; Muhammad Nawawi; Sari Muhiba; Atrika Iriani; Eva Novaria (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
ABSTRACT This study aims to analyze the budget allocation policy for the development of teacher pedagogical competence at Madrasah Ibtidaiyah Al-Adli Palembang towards the quality of learning. The development of teacher pedagogical competence is a crucial aspect in improving the quality of education. research related to this article using the library research method.This study aims to analyze the budget allocation for the development of teacher pedagogical competence at Madrasah Ibtidaiyah Al-Adli Palembang through the incremental budgeting model. This study examines how the principles of incremental budgeting are applied in the context of teacher competence development, especially pedagogical competence, including the budget preparation process, allocation priorities, and their relationship to teacher professional development needs. Keywords: Incremental Budgeting, Teacher Competency Development.